2011
DOI: 10.3892/etm.2011.441
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA potentiates the efficacy of 5-FU in Colo205 colon cancer cells in vivo through downregulation of P-gp and LC3-II

Abstract: Abstract. Traditional Chinese herbal medicines are widely accepted as an option for the treatment of colorectal cancers. Danshen (Salviae miltiorrhizae Radix) is widely prescribed in traditional Chinese medicine for cardiovascular diseases. Tanshinone IIA (Tan-IIA) is extracted from Danshen. Our previous studies have shown that Tan-IIA induces apoptosis in Colo205 human colon cancer cells in vitro and in vivo. In the present study, we investigated the efficacy of Tan-IIA and 5-fluorouracil (5-FU) in a Colo205 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…It's necessary to discover efficient pathway to impede the ectopic proliferation and accelerate death of tumor cells. Although, broad-spectrum anticancer drug such as 5-FU (a pyrimidine analogue) is widely used for clinical therapy (Gehoff et al, 2012;Pera et al, 2012;Su, 2012), the large side effects which it has been shown are a still limit aspect for use. Luteolin, a natural dietary flavonoid isolated from various plants has the potential role to slow or prevent the growth of tumor cell lines (Ko et al, 2002;Ju et al, 2007;Lim, et al, 2007;Chiu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It's necessary to discover efficient pathway to impede the ectopic proliferation and accelerate death of tumor cells. Although, broad-spectrum anticancer drug such as 5-FU (a pyrimidine analogue) is widely used for clinical therapy (Gehoff et al, 2012;Pera et al, 2012;Su, 2012), the large side effects which it has been shown are a still limit aspect for use. Luteolin, a natural dietary flavonoid isolated from various plants has the potential role to slow or prevent the growth of tumor cell lines (Ko et al, 2002;Ju et al, 2007;Lim, et al, 2007;Chiu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Among the major tanshinones isolated, cryptotanshinone, tanshinone I, tanshinone IIA, and dihydrotanshinone, tanshinone IIA have been shown to exert multiple anti-cancer activities including induction of * This work was supported by Hong Kong Baptist University Grants HKBU apoptosis and inhibition of angiogenesis and metastasis (8). Furthermore, tanshinones hold promise as sensitizing agents for chemotherapy and radiotherapy to enhance the cytotoxic effects of anti-cancer agents such as TNF-␣ (9), 5-fluorouracil (10), and ␥-irradiation (11). Recently, tanshinones have been found to induce ROS production in various types of cancer cells (12)(13)(14).…”
Section: Tnf-related Apoptosis Inducing Ligand (Trail)mentioning
confidence: 99%
“…In addition, Fu et al (25) found that TSA blocked the epithelial-mesenchymal transition through the downregulation of hypoxia-inducible factor-1α, reversing hypoxia-induced chemotherapy resistance in breast cancer cell lines. In addition, increasing evidence indicated that TSA can inhibit tumor cell growth and induce apoptosis (15,17,43); however, despite the fact that in certain type of cancer evidence showed that intrinsic apoptosis pathways were involved (14,44) (46) found that TSA potentiated the efficacy of 5-FU in colon cancer cells in vivo through the downregulation of P-glycoprotein and LC3-II. The results of the present study confirmed the antitumor activity and chemosensitizing effect of TSA in colon cancer cells and provided new evidence that TSA can sensitize colon cancer cells to 5-FU through the suppression of NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%